Studi Transposisi didaktik: Eksplorasi Taught Khowledge Pada Topik Pecahan Kelas V Sekolah Dasar - Unaenah, Een; Suryadi, Didi; Turmudi, Turmudi (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
Didactic transposition is an approach that allows the delivery of material more effectively and in accordance with student needs. The aim of this research is to explore how the concept of fractions is taught to fifth-grade elementary school students based on the didactic transposition approach. This research is part of didactic transposition research on fractional material, which consists of four stages: scholarly knowledge, knowledge to be taught, taught knowledge, and learned knowledge. Specifically, in this writing, the findings are presented only for the taught knowledge stage using qualitative research with descriptive methods. The results of the research show that the material presented in PBM shows a shift in knowledge on the concept of fractions from the concept of fractions as scholarly knowledge and knowledge to be taught to the concept of fractions as taught knowledge. This transition shows that there is a conceptual gap, both the concept gap between the concept definition presented by teachers in PBM as taught knowledge and the formal concept definition of scholarly knowledge, as well as the concept gap between the concept definition presented in PBM as taught knowledge and the concept definition presented in school mathematics textbooks as knowledge to be taught.